Latin sermon collections from later Medieval England : orthodox preaching in the age of Wyclif - Wenzel, Siegfried, 1928- (Cambridge studies in medieval literature., 2005)
Until the Reformation, almost all sermons were written down in Latin. Based on the extant manuscripts, this is the first systematic description and analysis of such collections of Latin sermons from the golden age of medieval preaching in England, the fourteenth and fifteenth centuries.